Effects of training and taper on blood leucocyte populations in competitive swimmers: relationships with cortisol and performance - Mujika, I.; Chatard, J. C.; Geyssant, A. (International Journal of Sports Medicine, 1996)
The effects of 12 weeks of training and 4 weeks of taper on blood leucocyte populations and cortisol were investigated in 8 well-trained competition swimmers. Blood samples were taken at rest in the mid-season (week 10), before taper (week 22) and after taper (week 26). Swimmers improving by more than 2% with taper (N = 4), efficient (GE), were compared with swimmers improving by less than 2% (N = 4), less efficient (GLE). No significant changes were observed in leucocyte subpopulations or cortisol during training. The percentage of neutrophils decreased during taper (p < 0.05). Basophils and the percentage of granulocytes tended to decrease, while lymphocytes tended to increase. The increment in lymphocytes was positively related with the reduction in training volume during taper (r = 0.86, p < 0.05). Cortisol levels did not change with taper and were not related with leucocyte status and kinetics. GE swimmers had higher pre- and post-taper eosinophil counts than GLE swimmers (p < 0.05). Lymphocyte counts in GE tended to be higher, too. Cortisol decreased with taper in GE, while it increased in GLE. In conclusion, taper appeared to have an influence on leucocyte populations, which did not seem to be related with blood cortisol.